Treatment of used ablution water from IIUM Masjid for reuse - Mamun, Abdullah Al; Muyibi, Suleyman Aremu; Abdul Razak, Nur Asilah (AENSI Publications, 2014)
Muslims have to conduct ablution before most of the religious rituals. This study was conducted at the International Islamic University Malaysia (IIUM) Masjid at Gombak Campus, which can accommodate about 9000 people during the special prayer times such as Jumma and Eid. The amount of water used for ablution only is calculated to be about 7 L/Cap.day. Unfortunately, the water used for ablution is discharged directly to the drain without any recycle and reuse. Quantity and quality of the used water after ablution was determined in this study. Laboratory tests on COD, TSS, TDS, turbidity and TN have indicated that, the used ablution water is not much polluted accept slightly high COD of 31 mg/L with respect to the Malaysian drinking water quality standards. As such, the used ablution water from the Masjid can be recycled and reused, after sand filtration, at least for general cleaning and landscaping purposes. On the other hand, treatment and reuse of commercial greywater would be too expensive in the contexts of Malaysian climate, where the rain-fed water is sufficiently available. It was realised that a low maintenance treatment system can be constructed to store, treat and reuse ablution water from the Masjid. For this purpose, size of the sand filter was determined for an overflow rate of 39.1 m/d. The treated water can be used for the landscaping and toilet flushing activities, which will reduce the water consumption in the university.